PENGEMBANGAN BAHAN AJAR BAHASA ARAB DENGAN PENDEKATAN KEMAHIRAN BERBICARA - M Kholison; Aidillah Suja; Cahya Edi Setyawan; Ramandha Rudwi Hantoro (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Teaching materials are one the crucial elements in the execution of the learning process, so an educator must be able to put up their best efforts to present teaching materials that can support learning goals. Teaching materials serve as a source of knowledge and media for learning, which is something that is crucial, especially to boost learning effectiveness and meet learning goals quickly and effectively. Education professionals must put the most effort into the preparation of teaching materials since they can utilize them to define the direction and goals of learning outcomes. As a result, the creation of teaching materials is crucial to the process of learning and teaching. There have been certain schools where learning Arabic has not been successful or efficient, particularly at the junior high school level. This is brought on by the wide range of educational backgrounds and limited Arabic proficiency of the students. Teachers and students therefore require educational tools that can enhance learning in order to address learning issues that may arise. The creation of instructional resources that are in line with student requirements and learning objectives is one of the learning innovations that may be used to address the aforementioned issues. In order to improve students' speaking abilities, this study intends to provide Arabic teaching materials.